Storytelling: The Next Step for Visualization - Kosara, R.; Mackinlay, J. (Computer (Long Beach, Calif.), 2013)
Presentation -- specifically, its use of elements from storytelling -- is the next logical step in visualization research and should be a focus of at least equal importance with exploration and analysis. [PUBLICATION ABSTRACT]